Physical activity and its clinical correlates in chronic thromboembolic pulmonary hypertension. (11th May 2021) - Schmidt, C; Monteiro, M; Reis, A; Santos, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Fundação para a Ciência (FCT) Coordenação de Aperfeiçoamento de Pessoal de Nível (CAPES) Background:  Limited data is available on physical activity (PA) levels in chronic thromboembolic pulmonary hypertension (CTEPH) patients, as well as on the impact of using different tools to assess PA such as questionnaires and accelerometers.  Purpose:  We aimed to quantify PA levels of CTEPH patients and study its clinical correlates, as well as to compare PA levels measured by the International Physical Activity Questionnaire (IPAQ) with measures from accelerometers. Methods:  This is a cross-sectional study (n = 50). Physical activity levels were measured using accelerometers and questionnaire (IPAQ). Clinical parameters evaluated were walked distance on the 6-minute-walking test (6MWT), pulmonary vascular resistance, N-terminal brain natriuretic peptide and quality of life (HRQoL) using the Cambridge Pulmonary Hypertension Outcome Review questionnaire. Results:  Accelerometer-derived data showed that CTEPH patients spent 60% of the recorded time in sedentary behaviours and only 2% in moderate-to-vigorous PA (MVPA). MVPA was mildly correlated with 6MWT (r = 0.359; p= 0.023) and symptom domain of HRQoL (r=-0.371; p = 0.044) but not with NT-proBNP, pulmonary vascular resistance or functional domain of HRQoL. Time spent in sedentary behaviour was lower in self-reported measurement (279 ± 165min/day) compared to accelerometry (446 ± 117min/day, p < 0.001). Self-reported MVPA was significantly higher than the one registered by the accelerometer (411 ± 569 vs. 131 ± 108 min/week, p = 0.027). Bland-Altman analysis indicated poor agreement between the two methods.  Conclusions:  Our results showed that CTEPH patients spend most of their days in sedentary behaviors and only a small amount of time in MVPA. MVPA was associated with symptoms domain of HRQoL and submaximal functional capacity. In addition, we showed a poor agreement between self-reported and accelerometer-derived PA in CTEPH patients, with the former overestimating the overall PA activity.